1976
DOI: 10.1080/00268977600102611
|View full text |Cite
|
Sign up to set email alerts
|

E.S.R. spectra of matrix isolated alkali atom clusters

Abstract: E.S.R. spectra assigned to Na3 molecules have been obtained by codepositing sodium atoms and diluent argon on a sapphire surface loosely coupled to a liquid helium cryostat and warmed by a heat leak, to allow aggregation before the alkali atoms are frozen into the argon matrix. The trimer spectra under these conditions were much more intense than the residual atom spectra. The trimer spectra indicate the unpaired electron in these molecules has predominantly s rather than p character. Approximately 95 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…There is no doubt, therefore, that Na, is a 'genuine' molecule with its unique electronic states and not merely a weak Van der Waals adduct of 3Na or Na2+Na as has been observed in cold supersonic beams of for example rare gas atoms, H2, H20 or C 0 2 molecules [58]. We are thus able to confirm and to extend the conclusion drawn by Lindsay et al [16] from the ESR. spectrum of Na,.…”
Section: 23supporting
confidence: 88%
“…There is no doubt, therefore, that Na, is a 'genuine' molecule with its unique electronic states and not merely a weak Van der Waals adduct of 3Na or Na2+Na as has been observed in cold supersonic beams of for example rare gas atoms, H2, H20 or C 0 2 molecules [58]. We are thus able to confirm and to extend the conclusion drawn by Lindsay et al [16] from the ESR. spectrum of Na,.…”
Section: 23supporting
confidence: 88%
“…Both the Fermi contact and the dipolar interaction constants are in complete disagreement with the picture resulting from the matrix studies. [39][40][41] We can only conclude that the influence even of a rare gas matrix on a Jahn-Teller molecule is strong enough to disturb the vibronic coupling effects severely. This is in contrast to recent work on Li 3 by Meyer, Demtröder, and co-workers.…”
Section: Discussionmentioning
confidence: 87%
“…21 Our prior optical-optical double resonance experiments 3 indicated that a large contribution to the hyperfine splittings of optical lines arises from considerable hfs coupling in the excited à and B states and we were aware that we might deal with the somewhat unusual case of stronger hyperfine coupling in the excited states than in the ground state. On the other hand, ESR spectroscopy of Na 3 in an argon matrix [39][40][41] yielded the result that the unpaired electron has a predominantly Na 3s character with about 10% admixture of 3p. Over 90% of the 3s population is equally distributed between the two terminal Na atoms and Ͻ10% is located at the apex atom.…”
Section: Discussionmentioning
confidence: 99%
“…With the goal of spectroscopic characterization, naked metal clusters in the absence of ligands are now being produced in the gas phase (9)(10)(11)(12) and through diffusion-controlled clustering in rare gas matrices (13)(14)(15)(16)(17)(18)(19). Although these experimental studies can provide detailed structural information, progress has been slowed by difficulties in making and correlating the measurements.…”
mentioning
confidence: 99%